2022
DOI: 10.2991/absr.k.220102.002
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Dolomite on Growth and Yield of Maize (Zea mays l.) in Dry Land

Abstract: The study had been conducted in dry land a site in East Java was in Kediri District during the rainy season I, 2018 -2019. The research was designed in RBD, 4 replicates, and 6 treatments, namely : A = without fertilizer, B = 300 Urea ha-1 + 400 kg NPK Phonska ha-1 (Recommended Rates of Inorganic Fertilizers or RRIF), C = RRIF + 1 ton dolomite ha-1, D = RRIF + 2 tons dolomite ha-1, E = RRIF + 3 tons dolomite ha-1, and F = RRIF + 4 tons dolomite ha-1. Data analysis used ANOVA (Analysis of Variance) and followed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 8 publications
2
8
0
Order By: Relevance
“…The number of leaves on the plant was the highest with a treatment of 1.0 t ha -1 DPR and when the application of the DPR was lower, the number of leaves per plant was not significantly different. The results were similar to those obtained by Soeparjono and Kadiyasari (2021) on black soybean, Suntoro et al (2018) and Krismawati et al (2022) on maize. When DPR was applied to ryegrass, the dry weight increased (Yang et al, 2012).…”
Section: Effects Of Dpr On Plant Height Number Of Leaves and Chloroph...supporting
confidence: 91%
See 1 more Smart Citation
“…The number of leaves on the plant was the highest with a treatment of 1.0 t ha -1 DPR and when the application of the DPR was lower, the number of leaves per plant was not significantly different. The results were similar to those obtained by Soeparjono and Kadiyasari (2021) on black soybean, Suntoro et al (2018) and Krismawati et al (2022) on maize. When DPR was applied to ryegrass, the dry weight increased (Yang et al, 2012).…”
Section: Effects Of Dpr On Plant Height Number Of Leaves and Chloroph...supporting
confidence: 91%
“…Phosphate rock is relatively slow to release soluble P; however, compared to industrial P fertilizers, phosphate fertilizer is low in price, making it a very appealing fertilizer (Hellal et al, 2019). Moreover, dolomite is rich in calcium and magnesium and it helps improve soil conditions, such as neutralizing pH and soil structure and helps plants develop good roots (Krismawati et al, 2022). According to Chutichude et al (2010), dolomite is frequently utilized as soil fertilizer in a variety of soils for agricultural applications..…”
Section: Introductionmentioning
confidence: 99%
“…4). Previous research showed a similar result, that dolomite application at acid soil in Centre Lampung could increase soil pH, increase soil Ca and mg and decrease soil Al 3+ [23].…”
Section: Nutrient Content Improvementsupporting
confidence: 62%
“…Increasing soil pH to neutral directly affects nutrients in the soil. The lime application can increase soil pH so that it can increase the availability of nutrients that can be absorbed by plants [8,9]. Measurement of soil nutrient status after the research indicated a decrease in soil nutrient levels (table 1).…”
Section: Soil Characteristicsmentioning
confidence: 99%